2016
DOI: 10.1088/1367-2630/18/11/113003
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on crystal and electronic structure of bismuth tellurohalides

Abstract: We study the possibility of pressure-induced transitions from a normal semiconductor to a topological insulator (TI) in bismuth tellurohalides using density functional theory and tight-binding method. In BiTeI this transition is realized through the formation of an intermediate phase, a Weyl semimetal, that leads to modification of surface state dispersions. In the topologically trivial phase, the surface states exhibit a Bychkov-Rashba type dispersion. The Weyl semimetal phase exists in a narrow pressure inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
7
25
0
Order By: Relevance
“…In most cases they connect the Weyl nodes within each - pair while in case of TeGe-QL-TeGe- termination the arcs connect points of neighboring pairs via the hole-like Rashba surface state which crosses the Fermi level twice in the - direction, however does it once in - and touches the Weyl nodes on the conduction band side. Similar effect of the Weyl nodes reconnecting has been observed recently in the TWS phase arising in BiTeI under pressure31.…”
supporting
confidence: 84%
“…In most cases they connect the Weyl nodes within each - pair while in case of TeGe-QL-TeGe- termination the arcs connect points of neighboring pairs via the hole-like Rashba surface state which crosses the Fermi level twice in the - direction, however does it once in - and touches the Weyl nodes on the conduction band side. Similar effect of the Weyl nodes reconnecting has been observed recently in the TWS phase arising in BiTeI under pressure31.…”
supporting
confidence: 84%
“…In contrast to the Rashba states, the surface electronic structure in topological insulators can be viewed as if the two branches have opposite dispersions and touch at a single point, i.e., at the Dirac point. The topological phase can be achieved in inversely stacked, centrosymmetric BiTeX and their thin films [23,24] and in BiTeX under external pressure [25,26] or via temperature-induced structure transformation [27]. In the latter case it was demonstrated that annealing of BiTeI leads to transformation into the Bi 2 Te 2 I phase, similar to the layered hexagonal, tetradymitelike compounds Bi 2 Te 3 and Bi 2 Se 3 (space group R3m), which currently are the most studied, both experimentally [28][29][30][31] and theoretically [32][33][34][35], three-dimensional topological insulators.…”
Section: Introductionmentioning
confidence: 99%
“…The Rashba semiconductor BiTeI, in particular, has been shown to undergo a pressure-controlled topological phase transition [14][15][16][17][18] . As this material is subjected to an increasing hydrostatic pressure it transitions from a non-topological phase to a strong topological insulator phase, at approximately 3 GPa [14][15][16][17] , and these two phases are separated by an intermediate Weyl phase [19][20][21] . Rashba semiconductors have generated much interest as a new material platform for spintronics and controlled topological phenomena [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%